(untitled) (Journal of Pakistan Orthopaedic Association, 2017)
Objective: To compare mean anterior knee pain score on cyclical kneeling at 12 weeks from intramedullary nailing for tibia shaft fractures with paratendinous approach versus transtendinous approach at a tertiary health care centre. Methods: 157 patients admitted with tibia diaphyseal fractures who subsequently underwent antegrade tibia nail insertion were enrolled in the study. The patients were divided in two groups. Group A consisted of patients underwent antegrade nail insertion using transtendinous approach and Group B underwent nail insertion using paratendinous approach. A standard study proforma was used to collect patient’s data and to record pain on kneeling on ground using a 100 mm Visual Analog Score (VAS). The assessment for pain was performed by a physician who wasblinded for the type of surgical approach that was used for nailing of tibia. Results: Mean age of patients in group A 35 ± 10 and in group B 36 ± 11 with P- value 0.655 which was statistically insignificant, similarly BMI was statistically insignificant as BMI 28 ± 6 and 26 ± 4 for group A and B respectively with insignificant P- value (0.073). After surgery, VAS scoring was done for anterior knee pain on cyclical kneeling at 12 weeks of surgery. Statistically, there was no significant difference in the score among the two study arms as 22 ± 8 and 21 ± 10 VAS evaluated in group A and B respectively with P- value (0.709). Conclusion: The choice of surgical approach, transtendinous versus paratendinous does not affect the outcome of antegrade tibia nailing with respect to anterior knee pain. There was no increase incidence of anterior knee pain associated with either of the two approaches. Therefore both approaches can be safely used to cite the entry portal for tibia nail insertion. Further detailed studies are required to study more causes of anterior knee pain. Key Words: Anterior Knee Pain, Intramedullary Nailing, Tibial Fractures.